Risk of second primary cancer among breast cancer patients: A systematic review and meta-analysis - Parhizgar, Parynaz; Bahadori Monfared, Ayad; Mohseny, Maryam; Keramatinia, Aliasghar; Hashemi Nazari, Seyed Saeed; Rahman, Syed Azizur; Al Marzouqi, Amina; Al-Yateem, Nabeel; Mosavi Jarrahi, Alireza (Frontiers in Oncology, 2023)
Objectives: The aim of this study was to estimate the excess risk of second primary cancer among breast cancer patients. Methods and Materials: This is systematic review. A comprehensive search of literature was performed in PubMed, Web of Science, Cochrane library, and Scopus. The search included all published studies up to October 2022. This systematic review included studies published in the English language that reported the risk of second primary non-breast cancer (i.e. SIR) among breast cancer patients older than 15 years. After evaluating the methodological quality of selected studies, standardized incidence ratios (SIRs) were pooled considering heterogeneity among studies. The estimates were pooled by age and time since diagnosis of primary breast cancer for both sexes (male and female). Age was categories based on before 50 and after 50 and time was categorised for duration of less than and more than 10 years. Results: from 2484 articles, 30 articles were eligible for inclusion in systematic review and meta-analysis. Studies varied in population, number of cases, study design, setting, and year of implementation of the research. The estimated SIR for men and women were 1.28 (95% CI: 1.18, 1.38) and 1.27 (95% CI: 1.15, 1.39), respectively. Women diagnosed with breast cancer before menopause (SIR: 1.52 (95% CI: 1.34, 1.71) vs. 1.21 (95% CI: 1.08, 1.34)), as well as women after 10 years since breast cancer diagnosis (1.33 (95% CI: 1.22, 1.431) vs. 1.24 (95% CI: 1.10, 1.37)), were at a higher risk for developing second primary cancer. Among men, while there were no differences in risk based on age, with the increase of time, the risk of second primary cancer reduced (SIR: 1.22 (95% CI: 1.12, 1.33) vs. 1.00 (95% CI: 0.79, 1.22)). Conclusion: There is an excess risk of second primary cancer among breast cancer patients. The excess risk should be considered for further screening and preventive measures among this population.